1960
DOI: 10.5636/jgg.11.125
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Viscosity of Magnetite

Abstract: Magnetic viscosity of ensemble of medium-sized grains of natural magnetites was examined at various temperatures.It was found that magnetic viscosity coefficient S, defined as I-I0=S(Q+logt) where I and I0 are intensity of magnetization at time t and t=0, is proportional to external magnetic field, and S is a linear function of temperature, except at temperatures close to the Curie point seems also that S tends to a finite value according as grain size tends to the order of a single domain.Further, the half li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

1966
1966
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 3 publications
4
27
1
Order By: Relevance
“…E(2 mm) displays only one peak just below T V . Above T V , in all three samples S A and S D are greatly reduced, but increase gradually on warming to 300 K. Samples W(11 μm) and H(23 μm) display a broad peak centered at 160-200 K. The large drop in viscosity rate on warming through T V is greater than that reported in other studies for SD [5] and MD [22] magnetite. (Fig.…”
Section: Viscous Magnetization Versus Temperaturecontrasting
confidence: 44%
See 1 more Smart Citation
“…E(2 mm) displays only one peak just below T V . Above T V , in all three samples S A and S D are greatly reduced, but increase gradually on warming to 300 K. Samples W(11 μm) and H(23 μm) display a broad peak centered at 160-200 K. The large drop in viscosity rate on warming through T V is greater than that reported in other studies for SD [5] and MD [22] magnetite. (Fig.…”
Section: Viscous Magnetization Versus Temperaturecontrasting
confidence: 44%
“…Shimizu [22] also found that the viscosity rate was also enhanced below the Verwey transition, but this time for MD magnetite, although this phenomenon was not discussed in the text. On comparison of the low-temperature disaccommodation spectra with the limited published low-temperature viscosity data, then there is reason to believe that disaccommodation will contribute significantly to the magnetic viscosity below T V, and it is this issue that this investigation addresses.…”
Section: Introductionmentioning
confidence: 95%
“…Theories of viscous magnetization in single domain magnetic grains were developed by Neel (1949A) and Brown (1959) and in multidomain grains by Neel (1949B), Stacey (1959), and Averyanov (1967. Laboratory experiments have substantiated these theories quite well (Barbier 1954, Shimizu 1960, Le Borgne 1960, Plessard 1961, Janovsky and Sholpo 1962.…”
Section: Theory Of Thermal Demagnetization Of Viscous Magnetizationmentioning
confidence: 87%
“…This may be explained by the experimental fact (Shimizu, 1960) that the viscosity magnetic field constant Sv of magnetite becomes maximum at about 200C.…”
Section: Resultsmentioning
confidence: 99%
“…6 Shows variation of magnetic viscosity field constant Sv as a function of absolute temperature (after Shimizu, 1960 (ii) VRM of magnetite grains (grain size J50u) produced with a longer application of a magnetic field becomes more resistant to the low-temperature demagnetization.…”
Section: Resultsmentioning
confidence: 99%